A Case of Severe Hemorrhagic Cystitis Caused by Melphalan with Successful Bladder Preservation by Ligation of Bilateral Internal Iliac Arteries - Takumi Takeuchi; Masayoshi Zaitsu; Koji Mikami; Yuta Takeshima; Takashi Matsunaga; Naohiko Okamoto; Sadao Imao (Case Reports in Medicine)
Hemorrhagic cystitis is a disorder which causes bleeding from diffusely inflammatory bladder mucosa. Here we present a case of severe hemorrhagic cystitis caused by melphalan. A 70-year-old man with multiple myeloma was presented with suddenly commenced massive gross hematuria. During an attempt of transurethral coagulation of bladder mucosa, bladder perforation into peritoneal cavity was suspected, then open laparotomy was indicated. We isolated bilateral internal iliac arteries and ligated them in order to control continued bleeding. After that, bladder bleeding was suddenly diminished. Ligation of internal iliac arteries may be a choice in controlling massive bleeding from bladder with severe hemorrhagic cystitis when laparotomy was inevitable.